1989
DOI: 10.1161/01.cir.80.4.903
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and beta-adrenergic receptor adaptations during long-term beta-adrenoceptor blockade. Studies with acebutolol, atenolol, pindolol, and propranolol in hypertensive patients.

Abstract: In an attempt to further clarify the mechanism of the maintenance of the antihypertensive effect of beta-adrenoceptor antagonists, the effects of four antagonists with different ancillary properties (acebutolol, atenolol, pindolol, and propranolol) on systemic and renal hemodynamics, body fluid volumes, hormones, and lymphocyte beta-adrenoceptor density were studied in four groups of 10 hypertensive patients. The patients were observed for 3 weeks during active treatment and for 2 weeks after withdrawal of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…Nevertheless, this is in agreement with other reports, which found the restoration of CO occurs after the administration of timolol and atenolol, two i-blockers devoid of ISA [29,30]. Furthermore, the restoration of CO after longterm administration has also been confirmed by comparing the long-term administration of atenolol and propranolol, i-blockers devoid of ISA, with AC, a i-blocker that possesses ISA [31].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, this is in agreement with other reports, which found the restoration of CO occurs after the administration of timolol and atenolol, two i-blockers devoid of ISA [29,30]. Furthermore, the restoration of CO after longterm administration has also been confirmed by comparing the long-term administration of atenolol and propranolol, i-blockers devoid of ISA, with AC, a i-blocker that possesses ISA [31].…”
Section: Discussionsupporting
confidence: 92%
“…Waagstein et al reported in their recent paper [30] that a 60% increase in receptor density was observed after beta blockade. In our data, a similar result was obtained [8], although the beta-receptor assay was carried out using peripheral lymphocytes [34]. However, since the changes in receptor density may occur in a week [9,32], such a beneficial long-term effect cannot be explained by upregulation only.…”
Section: Fig 4 a Comparison Of Groups I (Beta-blocker Group) And Grsupporting
confidence: 83%
“…However, in severe heart failure, where there is high level of sympathetic tone, abrupt induction of beta blockade should be cautioned. ISA is unlikely to be suitable for the treatment of heart failure, probably because beta blockers with ISA might not relatively induce upregulation of beta adrenoceptors [34].…”
Section: Fig 4 a Comparison Of Groups I (Beta-blocker Group) And Grmentioning
confidence: 99%
“…Atenolol lowered systolic BP and PP less than PER/IND. As previously highlighted by other researchers 22 and ourselves, 12,13 this difference is largely the consequence of the AT-induced reduction of heart rate, which is responsible for a return of the wave reflections in the central arteries during systole. This timing precludes a lowering of the central systolic blood pressure.…”
Section: Discussionmentioning
confidence: 57%
“…b-Blockers without intrinsic sympathomimetic activity, such as AT, decrease heart rate and cardiac output and increase total peripheral resistance, although the latter effect is blunted in the long-run. 22 Angiotensinconverting enzyme inhibitors, such as perindopril, cause vasodilatation with inhibition of the reactive neurohumoral activation, increase muscular blood flow and have no negative inotropic effect on the myocardium. 23 aPWV, which is determined in the most pulsatile segment of the arterial circulation, 24 is the gold standard for measuring arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%